Histoire de la première imprimerie de Lima et d'un manuscrit redécouvert, El primer nueva corónica y buen gobierno de Felipe Guaman Poma de Ayala - Gimena Fernández (Nuevo mundo - Mundos Nuevos, 2013)
The first printing press moved to Peru in the late sixteenth century, on the occasion of the edition, in 1584, of the Doctrina Christiana there Cathecismo para la instrucción de los Indios, the first trilingual catechism in Spanish, Quechua and Aymara by the Italian typographer Ricardo. Until then, everything arriving to the colonies came from Spain and was published under the control of the Crown and the Church. The circulation of knowledge was entrusted to various religious orders that were intended for the evangelization of the indigenous populations. The first printed materials were catechisms, confessionals, vocabularies and dictionaries. Chronicles and relaciones continued to be printed in Europe under strict censorship laws till the first half of the seventeenth century. All manuscripts had to obtain a license issued by the Council of the Indies, and therefore, having been presented to the colonial authorities in Lima, were to be sent to the old continent. On the way to Europe, some manuscripts were lost. This is the case of El primer nueva Coronica y buen gobierno by Felipe Guaman Poma de Ayala, found three centuries after it was written on the other side of the ocean, in Denmark, among the treasures of the Royal Library of Copenhagen.